(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Sudha Murthy is an Indian woman writer in Kannada and English. Sudha Murthy’s women protagonists are all drawn from the middle-class family set up and are sensitive, intelligent, educated and career-oriented. Above all Sudha Murthy’s portrayal of women stirs out a universal reach out of their problems. Her works draw on the subtle factors and besetting influences contributing to the none-too-happy position of women in the emerging Indian society. Women firstly find themselves trapped in the roles assigned to them by the society and later on attempt to assert their individuality. Sensitive to the changing times and situations they revolt against the traditions in their search for freedom and eventually succeed in achieving self-identity and independence. The writer presents varied mood and tone in her works with the central being feminist approach.